Mapping Cases and Actors in Violations of Religious Freedom in Contemporary Madura - Abd Hannan; Ach. Fatayillah Mursyidi (Tribakti: Jurnal Pemikiran Keislaman, 2024)
This study examines the dynamics of violations of the freedom of religion in Madura, mapping cases, actors, and handling models. This study is field research that uses qualitative research with a phenomenological approach. Methodologically, the choice of the qualitative type is based on the research objectives that want to describe the research problem in depth and focus. The research problem is to examine the dynamics of violations of freedom of religion in Madura, mapping cases, actors, and handling models of religious sociology. After analyzing the field data based on the perspective of the sociology of religion, this study found that cases of violations of freedom of religion in Madura tend to occur in the internal scope of the Muslim community, which is generally triggered by the attitude of 'resistance' to the dimensions of freedom of religion or belief, both dimensions of forum internum and forum externum. Based on these actors, the practice of violating the freedom of religion in Madura often involves religious figures. In this context, kyai is the most influential figure as well as the highest religious authority in Madura. In addition, other actors also come from mass organizations or religious groups, which in fact have great power and influence to mobilize the masses, as in the violation of freedom of religion that befell Shia Sampang adherents and Wahabi Muslims in Pamekasan. Regarding handling, the model of handling violations of freedom of religion in Madura has so far been more exclusive. The settlement process tends to produce unbalanced decisions, often centered and in favor of the majority group or groups, especially the local elite circle such as Kyai. In many cases, the handling process is not fully aimed at building a truly accommodative and moderate agreement, but rather at maintaining the status quo, creating domination, intimidation, and even religious intervention against minority groups.